Early Childhood Value and Character Construction through Great Child Habituation Content on social media: An Analysis of Adaptive Parenting Modelling Practices and Design - Alfi Rohmatul Azizah; Alif Mudiono; Eny Nur Aisyah (International Islamic Schools Alliance, 2026)
The present study has been developed for the purpose of analyzing the process of establishing early childhood values and characteristics in the context of